Clinical significance of intramammary arterial calcifications in diabetic women - Milošević Zorica; Bjekić Jelica; Radulović Stanko; Goldner Branislav (Vojnosanitetski Pregled)
Background. It is well known that intramammary arterial calcifications diagnosed by mammography as a part of generalized diabetic macroangiopathy may be an indirect sign of diabetes mellitus. Hence, the aim of this study was to determine the incidence of intramammary arterial calcifications, the patient’s age when the calcifications occur, as well as to observe the influence of diabetic polineuropathy, type, and the duration of diabetes on the onset of calcifications, in comparison with nondiabetic women. Methods. Mammographic findings of 113 diabetic female patients (21 with type 1 diabetes and 92 with type 2), as well as of 208 nondiabetic women (the control group) were analyzed in the prospective study. The data about the type of diabetes, its duration, and polineuropathy were obtained using the questionnaire. Statistical differences were determined by Mann-Whitney test. Results. Intramammary arterial calcifications were identified in 33.3% of the women with type 1 diabetes, in 40.2% with type 2, and in 8.2% of the women from the control group, respectively. The differences comparing the women with type 1, as well as type 2 diabetes and the controls were statistically significant (p=0.0001). Women with intramammary arterial calcifications and type 1 diabetes were younger comparing to the control group (median age 52 years, comparing to 67 years of age, p=0.001), while there was no statistically significant difference in age between the women with calcifications and type 2 diabetes (61 years of age) in relation to the control group (p=0.176). The incidence of polineuropathy in diabetic women was higher in the group with intramammary arterial calcifications (52.3%) in comparison to the group without calcifications (26.1%), (p=0.005). The association between intramammary arterial calcifications and the duration of diabetes was not found. Conclusion. The obtained results supported the theory that intramammary arterial calcifications, detected by mammography could serve as markers of co-existing diabetes mellitus and therefore should be specified in radiologic report in case of their early development.